Types and content of education - Gafurova N (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The content of the educational process, education - a specific, clear goal and the process of comprehensive development of a person based on socio-historical experience, formation of his consciousness, behavior and worldview are revealed in the article. It has been deeply analyzed that education is a process of activity aimed at bringing the young generation to adulthood in all respects towards a specific goal, forming social consciousness and behavior in it.